Political Communication on Social Media: The Analysis of YouTube Advertisements for March 31, 2019 Local Elections - Şükrü Balcı; Hamide Sarıtaş (Türkiye İletişim Araştırmaları Dergisi)
In recent years, social media applications have been remarkably used in providing political informationand participation. Social media is approached as a new meeting area where political actors and votersinteract in political communication. Politicians actively and effectively use this medium during and beyondtheir election campaigns, particularly YouTube, which allows to see the number of views, the opportunityto comment on the videos and direct sharing. This article analyses the use of YouTube as a politicalcommunication medium by Turkey’s five most popular political parties represented in the Grand NationalAssembly; AK Party, CHP, HDP, MHP and IYI Party; during March 31, 2019 Local Elections. The sample ofthis research consists of 120 political advertisements published on these political parties’ official YouTubechannels. The political advertisements were analysed by content analysis technique as a qualitative researchmethod. According to the findings, the parties mostly prefer positive advertising language as an electionstrategy. In addition, we determined that the political advertisements published by CHP were closed to userinteraction, and the other parties did not publish replies to the user comments on their advertisements.In sum, this paper argues that the parties utilized YouTube for promotion purposes in the same way astraditional media tools during this election period.